2008
DOI: 10.1016/j.adolescence.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Latino adolescents' academic success: The role of discrimination, academic motivation, and gender

Abstract: Guided by the academic resilience perspective, the current longitudinal study examined whether academic motivation mediated the relation between Latino adolescents' (N = 221) experiences with discrimination and their academic success. The potential moderating role of gender was also examined. Using multiple group analysis in structural equation modeling, findings indicated that perceived discrimination at Wave 2 significantly predicted academic motivation at Waves 2 and 3 for boys but not girls. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 45 publications
10
148
1
9
Order By: Relevance
“…Females not only tend to perceive more discrimination than males, but the association between perceived discrimination and negative developmental consequences (with the exception of self-esteem) is often weaker (or nonexistent) for females than it is for males (Alfaro et al, 2009;Almeida et al, 2009;Behnke et al, 2011;Benner & Graham, 2011;Seaton et al, 2010). As noted above, adolescents' perceptions of discrimination increase over time; however, research indicates that this increase may occur at a slower rate for females than for males (Benner & Graham, 2011).…”
Section: Gendermentioning
confidence: 81%
See 1 more Smart Citation
“…Females not only tend to perceive more discrimination than males, but the association between perceived discrimination and negative developmental consequences (with the exception of self-esteem) is often weaker (or nonexistent) for females than it is for males (Alfaro et al, 2009;Almeida et al, 2009;Behnke et al, 2011;Benner & Graham, 2011;Seaton et al, 2010). As noted above, adolescents' perceptions of discrimination increase over time; however, research indicates that this increase may occur at a slower rate for females than for males (Benner & Graham, 2011).…”
Section: Gendermentioning
confidence: 81%
“…Numerous studies have demonstrated the significant negative associations among perceived discrimination and academic outcomes including GPA, academic motivation, academic goals, and perceived academic efficacy (Alfaro, Umaña-Taylor, Gonzales-Backen, Bámaca, & Zeiders, 2009;Smalls, White, Chavous, & Sellers, 2007;Tabbah, Miranda, & Wheaton, 2012;Wong et al, 2003). These effects hold true both for males and females, but as previously mentioned, males are generally at greater risk for more negative outcomes in most developmental domains.…”
Section: Academic Achievement Outcomesmentioning
confidence: 82%
“…For instance, in a study of Latino adolescents, perceived discrimination was significantly associated with poorer academic outcomes among male adolescents, but not their female counterparts (Alfaro et al, 2009). Findings such as these have prompted scholars to question whether discrimination may be more consequential for boys than girls; as such, we examined potential moderation by gender in all analyses.…”
Section: The Present Studymentioning
confidence: 99%
“…These experiences have been associated with psychological distress (Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003), decreased psychological well-being (Sellers, CopelandLinder, Martin, & Lewis, 2006;Umaña-Taylor & Updegraff, 2007), and declines in grades, academic curiosity, and persistence (Alfaro, Umaña-Taylor, Gonzales-Backen, Bámaca, & Zeiders, 2009;Neblett, Philip, Cogburn, & Sellers, 2006;Wong, Eccles, & Sameroff, 2003). Moreover, it appears that the impact of discrimination may be particularly deleterious for African American youth.…”
mentioning
confidence: 99%
“…On the other hand; the study conducted by Tabancalı and Kazım [52] with the students from different departments of education faculty, the study conducted by Akbaş and Çekilelli [43] on physical science teaching of pre-service form teachers, and the study conducted by Sandıkçı and Öncü [54] on the occupational self-efficacy perceptions of pre-service PE teachers showed that there was no difference by gender. However, many studies on academic success found that women had higher academic success than men [55,56] as there was a positive correlation between academic success and academic self-efficacy [47][48][49]57]. In our study, the differences in the academic self-efficacy perceptions of PE teacher candidates may be due to women's desire and needs to participate in the work force and obtain economic independence and participate in social life and to be liberated when social and cultural factors are taken into consideration.…”
Section: "Research Question 2 Are the Occupational Anxiety And Academentioning
confidence: 99%